PENDAMPINGAN PENGEMBANGAN GEBLEK PEDAS PADA WIRAUSAHAPEMBUATAN GEBLEK DI DUSUN DUSUN BALONG V, DESA BANJARSARI, KECAMATAN SAMIGALUH, KULON PROGO, YOGYAKARTA - Susilo Wibisono (UII, 2015)
Geblek is a typical food of Kulon Progo made from starch or tapioca starch. Thisfood has a typical globular form a number eight shape and aslightly chewy texture. Geblekvery famous in Kulon Progo and surroundings, thus becoming one of the icon culinaryKulon Progo. It makes geblek is easy to find in Kulon Progo. As an entrepreneur geblek,innovate an obligation to succeed. A recent study byDeloitte Touche Tohmatsu Limitedrevealed that 78% of the